INNOVATION IN CONSTRUCTION MANAGEMENT - Pritesh S.Shejwal; Dhawani Prajapati; Rahul Kulchandani (International Journal of Innovations in Engineering Research and Technology, 2021)
The construction industries in the 21stcentury are passing through revolution in terms of the change in material production methods, construction technology and innovative machines to support the construction activities. The construction industry was facing many problems on the issues like project management, management of the material, cost of the material and proper implementation of the processes. The technology has helped the construction industry to improve the performance and as a result in the developing countries like India many mega projects are coming up. The construction industries with the technology implementation are handling very challenging projects and delivering it in time. Authors have presented the overview of the innovation in the construction industries